The diplomacy of resistance: power, hegemony and nuclear disarmament. Issue 2 (4th May 2018) - Ritchie, Nick; Egeland, Kjølv
ABSTRACT: The humanitarian initiative for nuclear disarmament has challenged and transformed global nuclear politics. Aimed at delegitimising nuclear weapons as acceptable instruments of statecraft, the initiative has been backed by many civil society organisations and most non-nuclear-weapon states. The nuclear-weapon states, however, have opposed the initiative, accusing it of undermining the Nuclear Non-Proliferation Treaty and destabilising nuclear politics. Conceptualising a 'diplomacy of resistance', this article positions the humanitarian initiative as a transnational social movement and traces its development through practices of resistance and counter-resistance. Drawing on Robert Cox's conception of resistance as counter-hegemonic and Michael Barnett and Raymond Duvall's taxonomy of power, the article explores the nexus of power and resistance in global nuclear politics. We explain the humanitarian movement's specific aims and practices as a function of its champion's relative political weakness vis-à-vis the nuclear-weapon states. The movement's coherence and effectiveness, in turn, was fostered by a coalitional logic that allowed different identities of resistance to be steered towards a nuclear ban treaty within the UN's institutional framework.